Turning Leadership Upside-Down and Outside-In During the COVID-19 Pandemic - Briscoe, Patricia; Nyereyemhuka, Nyasha (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2022)
COVID-19 has led many to question how education and schooling are supposed to continue in a world of uncertainty. This case follows the journey of Mariam, an Ontario elementary school principal, as she pivoted her leadership while transitioning between in-person and virtual schooling during the COVID-19 pandemic. The case narrative describes the events that turned Mariam’s leadership upside-down and required her to adapt to meet the needs of the school community; in the process, however, she forgot about her own needs. Crisis leadership forced her to learn, unlearn, and relearn her beliefs about her leadership choices and purpose. The case includes teaching notes and two activities: (a) using a crisis leadership framework for reflecting on the learning, unlearning, and relearning of education, schooling, and the purpose of educational leadership during a pandemic, and (b) strategies to help leaders refocus from the outside in using self-care. Instructors can use this case in graduate-level leadership courses and for professional development.